Special Care Dentistry in a Patient with Prader-Willi Syndrome through the Use of Atraumatic Restorative Treatment under General Anesthesia - Caio Vinícius Gonçalves Roman-Torres; Sérgio Takashi Kussaba; Yasmin Comoti Vita Bantim; Roberta de Barros Antunes Almeida de Oliveira (Hindawi Limited, 2017)
Prader-Willi syndrome described in 1956 has a genetic origin, affecting both genders, varying in presence and intensity from individual to individual. A precocious diagnosis, before the manifestation of symptoms, has brought some improvement in the quality of life of the carriers in the last years. The objective of this case report was to describe the treatment realized in a 3-year-old boy who presented grade II obesity, difficulty of locomotion, hypotonia, and history of cardiopathy. A dental treatment under general anesthesia was defined, allowing an oral adequation in a single section, in which it was planned the extraction of the element 74 and atraumatic restorative treatment (ART) technique in the other teeth. The precocious intervention in this 3-year-old patient by the therapy realized with ART under general anesthesia was done with success, avoiding unnecessary extractions, preserving dental elements, and maintaining the oral cavity in adequate function.